A Longstanding Duality: Discursive Construction of the EU vs the UK in the British Broadsheets’ News Discourse of the Brexit Referendum - Javadinejad, Arash (International Journal of English Studies, 2024)
The relationship between the United Kingdom and the European Union has always been tumultuous and problematic, and European integration has always been a controversial topic in the UK’s contemporary politics. However, current research on the Brexit referendum’s news discourse hardly addresses this topic directly. Therefore, this paper analyses the discursive construction of the UK versus the EU during the campaign coverage of the Brexit referendum in major British broadsheets. To do so, a corpus of four major British broadsheets along ideological lines (left-right) and Brexit stance (Leave-Remain) was analysed by applying a mixed method approach of Corpus Assisted Discourse Studies (Discursive News Values Analysis along with some Corpus Linguistic tools and techniques). The way news values were adopted in the campaign coverage of the British broadsheets shows a certain continuation of historical discourses around the relationship of the entities. The results show that news values during the campaign coverage were adopted by the pro-leave outlets to construct a highly negative and elite-associated image of the EU in contrast to the UK, while the pro-remain broadsheets mostly focused on a limited, practical and economic argument in favour of the EU, maintaining and highlighting the importance of UK independence.